The Philosophy and Methodology of Islam-Science Integration: Unravelling the Transformation of Indonesian Islamic Higher Institutions - Khozin Khozin; Umiarso Umiarso (Ulumuna, 2019)
The transformation of Islamic higher education into State Islamic University (Universities Islam Negeri/UIN) necessitates the changing of scientific thoughts. Before this transformation, Islamic higher education 's core business is commonly concerned with the teaching of Islamic sciences, while UIN includes the instruction of general sciences, e.g., natural and social Sciences. In fact, the two (Islamic and natural-social science) should be integrated into the Islamic high education to establish a new integrated scientific paradigm. This study focuses mainly on the philosophy and the integration of science and Islamic methodologies in Indonesia. Based on the phenomenological qualitative approach, the current study critically examines Islam and science integration. Grounded on the study of three UINs, the article shows a novel paradigm that enables the integration of science and religion in those universities. Each university offers a specific character of the integration. UIN of Malang, for example, initiates the integration which is reflected in “tree of science”. UIN of Yogyakarta offers the metaphor of “spider web” for its interconnected and integrated Islam and science project while UIN of Surabaya proposes multidisciplinary-integration with the metaphor of integrated twin towers.